Pengembangan Sains pada Anak Usia Dini dalam Perspektif Filsafat Ilmu - Kusumawati, Dhian Kurnia (Indo-MathEdu Intellectuals Journal, 2023)
The astonishing social and economic changes of the past three decades have been heavily influenced by economic developments driven by the application of technology. Researchers aim to develop individuals to recognize the scope of science in early childhood and be able to use fundamental aspects in solving the problems they face. So, the focus of science learning development programs should be aimed at fostering early childhood understanding, interest and appreciation of the world in which they live in these things in general conveying that the development of science learning in early childhood, this type of research includes research on library materials (Library Research) is research conducted in libraries and uses reading materials in the form of books, magazines, or others. Whereas when viewed in terms of the way and level of discussion of problems, this type of research uses Descriptive research, Science has a limited scope on things that can be understood by our senses such as sight, hearing, touch, touch and speech, Science is a series of concepts and conceptual schemes that relate to each other, and grow as a result of experimentation and observation,  As well as useful to observe, explore and experiment further